Exfoliated near infrared fluorescent silicate nanosheets for (bio)photonics - Selvaggio, Gabriele; Chizhik, Alexey; Nißler, Robert; Kuhlemann, llyas; Meyer, Daniel; Vuong, Loan; Preiß, Helen; Herrmann, Niklas; Mann, Florian A.; Lv, Zhiyi; Oswald, Tabea A.; Spreinat, Alexander; et al. (Nature communications, 2020)
Imaging of complex (biological) samples in the near-infrared (NIR) is beneficial due to reduced light scattering, absorption, phototoxicity, and autofluorescence. However, there are few NIR fluorescent materials known and suitable for biomedical applications. Here we exfoliate the layered pigment CaCuSi 4 O 10 (Egyptian Blue, EB) via ball milling and facile tip sonication into NIR fluorescent nanosheets (EB-NS). The size of EB-NS can be tailored to diameters <20 nm and heights down to 1 nm. EB-NS fluoresce at 910 nm and the fluorescence intensity correlates with the number of Cu 2+ ions. Furthermore, EB-NS display no bleaching and high brightness compared with other NIR fluorophores. The versatility of EB-NS is demonstrated by in-vivo single-particle tracking and microrheology measurements in Drosophila melanogaster embryos. EB-NS can be uptaken by plants and remotely detected in a low-cost stand-off detection setup. In summary, EB-NS have the potential for a wide range of bioimaging applications. Near-infrared (NIR) fluorophores have attracted interest for bioimaging; yet availability, biocompatibility and application can be an issue. Here, the authors report on the development of Egyptian Blue nanosheets with high NIR fluorescence and photostability demonstrating bioimaging applications in vivo.